PENINGKATAN KETERAMPILAN MENULIS TEKS PROSEDUR PADA SISWA KELAS XI SMA NEGERI 1 LAUBALENG BERBASIS KEARIFAN LOKAL MERDANG MERDEM PADA MASYARAKAT KARO - monika bangun (Jurnal Bahastra, 2021)
AbstractThis study aims to improve student learning outcomes in procedural texts based on merdang merdem local wisdom in SMA Negeri 1 Laubeleng. This type of research is Classroom Action Research. The subjects of this study were 32 students of class XI consisting of 13 male students and 19 female students. This research was conducted in two cycles, each cycle having one meeting. The techniques used are interviews, tests. Data analysis is used to determine the average student learning outcomes by determining individual completeness, classical completeness, and the average student learning outcomes according to the specified minimum completeness criteria (KKM), namely 70. The results of the research conducted in the first cycle obtained the results of the implementation of learning in teacher activities, namely 60 in the sufficient category, while in the remaining activities, the value of 56 was in the sufficient category. Classical learning outcomes obtained by students who completed 21,87% and those who did not complete 68.75%, the average value of student learning outcomes in cycle I was 52.62 with student learning outcomes in cycle I not very maximal, thus proceeding to next cycle. The results of the research in cycle II obtained the results of the implementation of learning at the teacher's activity that was 89% in the good category, while in the student activity, the score was 80 in the good category. The completeness of individual student learning outcomes was 30 students while the students who did not complete were 2 students. Classical student learning outcomes obtained by students who completed 93.75% and students who did not complete 6.25% of the average value of student learning outcomes in cycle II increased to 81,90. Key Words: Writing Procedure Text, Local wisdom merdang merdem.